2007
DOI: 10.1534/genetics.106.061929
|View full text |Cite
|
Sign up to set email alerts
|

Genes Affecting Cell Competition in Drosophila

Abstract: Cell competition is a homeostatic mechanism that regulates the size attained by growing tissues. We performed an unbiased genetic screen for mutations that permit the survival of cells being competed due to haplo-insufficiency for RpL36. Mutations that protect RpL36 heterozygous clones include the tumor suppressors expanded, hippo, salvador, mats, and warts, which are members of the Warts pathway, the tumor suppressor fat, and a novel tumor-suppressor mutation. Other hyperplastic or neoplastic mutations did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
184
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(189 citation statements)
references
References 81 publications
5
184
0
Order By: Relevance
“…Thus, loss of Hippo pathway activity or elevated levels of Yki activity result in hyperproliferation of imaginal disc cells and resistance to apoptosis that normally would eliminate extra cells (21). Notably, an increase in Yki activity can rescue weak cells, such as cells heterozygous for Minute (M) mutations, from being eliminated by cell competition (22). M mutations occur in ribosomal proteinencoding genes and were the first class of genes identified as having cell-competition phenotypes (23).…”
mentioning
confidence: 99%
“…Thus, loss of Hippo pathway activity or elevated levels of Yki activity result in hyperproliferation of imaginal disc cells and resistance to apoptosis that normally would eliminate extra cells (21). Notably, an increase in Yki activity can rescue weak cells, such as cells heterozygous for Minute (M) mutations, from being eliminated by cell competition (22). M mutations occur in ribosomal proteinencoding genes and were the first class of genes identified as having cell-competition phenotypes (23).…”
mentioning
confidence: 99%
“…For example there is differing data concerning the degrees to which Dpp is a survival signal or Jun Kinase activity required for competitive cell death. 5,7,[9][10][11] It has been suggested that Myc levels could also affect Dpp capture. 6 However, other workers have proposed that cells with higher Myc might send a non-autonomous killing signal that is independent of Dpp.…”
Section: Competition Affects Cell Survivalmentioning
confidence: 99%
“…Screens have previously been performed to identify genes that are needed in the cells that lose competitions. 7,9 …”
Section: Eat To Competementioning
confidence: 99%
See 2 more Smart Citations